Herpes Simplex Virus Encephalitis in Geriatric Patients - TUFAN ÇİNÇİN, ASLI; SİLİ, ULUHAN (SPRINGER, 2017)
Purpose of Review Herpes simplex virus encephalitis (HSVE) is a rare, devastating infectious disease of the brain. We reviewed published case series to determine whether epidemiology, clinical characteristics, and prognosis of HSVE differed in geriatric patients. Recent Findings Geriatric patients have a higher incidence of HSVE and a worse prognosis than the rest of the adult population. Summary The gold standard to confirm HSVE diagnosis is to demonstrate HSV DNA in cerebrospinal fluid using polymerase chain reaction. Antiviral treatment with acyclovir prevents HSVE-related morbidity and mortality if started on time. Diagnosis and treatment of HSVE pose specific challenges due to comorbidities and medical conditions presenting with similar signs and symptoms commonly encountered in geriatric medicine. Thus, timely empirical treatment and confirmation of diagnosis in this patient population relies largely on astuteness of the clinician.
Keywords: Herpes simplex encephalitis; Central nervous system infections; Encephalitis; Herpes simplex virus; Geriatrics; CENTRAL-NERVOUS-SYSTEM; NMDA RECEPTOR ENCEPHALITIS; AUTOIMMUNE ENCEPHALITIS; ADULT PATIENTS; DIFFERENTIAL-DIAGNOSIS; EMERGENCY-DEPARTMENT; VIRAL ENCEPHALITIS; CLINICAL APPROACH; ELDERLY-PEOPLE; ACYCLOVIR